Development of a Human Resources Processes Model Based on the AMO Approach in the Iraqi Volleyball Federation - Alabedi, Mohammed Kadhim Jabbar; Moshkelgosha, Elham; Abdulkareem khudhair, Karrar; Zamani Nukaabadi, Alireza (Management Strategies and Engineering Sciences, 2024)
The aim of this study is to develop an integrated model of human resource processes based on the AMO approach in the Iraqi Volleyball Federation. This research is applied in purpose, descriptive-survey in terms of data collection, and qualitative in nature. The data analysis was conducted using thematic analysis. The statistical population of this study consisted of experts from the Iraqi Volleyball Federation and university professors in the field of sports management in Iraq. A purposive sampling method was employed, selecting 16 individuals from the Federation’s members, university professors specializing in sports management, and human resources management specialists using snowball sampling. The results of the analysis of the interviews revealed that the codes extracted from 16 interviews amounted to 315 initial codes, from which 46 primary themes were derived. Ultimately, the extracted themes were named and categorized into three final themes based on the AMO model: green ability, green motivation, and green opportunities. The AMO model, focusing on enhancing employees' capabilities, creating participation opportunities, and promoting motivation, can contribute to improving organizational efficiency. The findings also indicate that employee training and development of skills, as well as the creation of reward systems aligned with desired behaviors, are key success factors in implementing this model.